The Chan Hol cave near Tulum (Quintana Roo, Mexico): evidence for long-lasting human presence during the early to middle Holocene - Hering, Fabio; Stinnesbeck, Wolfgang; Folmeister, Jens; Frey, Eberhard; Stinnesbeck, Sarah; Avilés, Jerónimo; Núñez, Eugenio Aceves; González, Arturo; Terrazas Mata, Alejandro; Benavente, Martha Elena; Rojas, Carmen; Velázquez Morlet, Adriana; et al. (Journal of quaternary science, 2018)
Numerous charcoal accumulations discovered in the submerged Chan Hol cave near Tulum, Quintana Roo, Mexico, have been 14C-dated revealing ages between 8110 ± 28 14C a BP (9122-8999 cal a BP) and 7177 ± 27 14C a BP (8027-7951 cal a BP). These charcoal concentrations, interpreted here as ancient illumination sites, provide strong evidence that the Chan Hol cave was dry and accessible during that time interval. Humans used the cave for at least 1200 years during the early and middle Holocene, before access was successively interrupted by global sea level rise and flooding of the cave system. Our data thus narrow the gap between an early settlement in the Tulum area reaching from the late Pleistocene (∼13 000 a) to middle Holocene (e.g. 7177 14C a BP), and the Maya Formative period at approximately 3000 a bp. Yet, no evidence has been presented to date for human settlement during the ∼4000-year interval between 7000 and 3000 a. This is remarkable as settlement in other areas of south-eastern Mexico (e.g. Chiapas, Tabasco) and in Guatemala was apparently continuous.